2007
DOI: 10.1007/s00246-006-0014-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Plasma B-Type Natriuretic Peptide with Shunt Severity in Patients with Atrial or Ventricular Septal Defect

Abstract: The goal of this study was to test the utility of bedside plasma concentration of B-type natriuretic peptide (BNP) assay as a screen for large shunts in pediatric patients with atrial septal defects (ASDs) and ventricular septal defects (VSDs). Thirty-five children at a mean age of 70+/-129 weeks with ASD or VSD were included in the study. Nine patients had VSD and 26 had ASD. Plasma BNP values were compared with the Qp/Qs ratios derived from quantitative Doppler flow measurements. Mean BNP was 29+/-42 pg/ml, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 14 publications
0
30
0
3
Order By: Relevance
“…In heart disease due to a left-to-right shunt, such as ASDs and VSDs, NT-proBNP levels are high when the Qp/Qs is high, and the fact that this decreases after surgery indicates that congestive HF due to volume overload may result in increased NT-proBNP levels. [41][42][43] Moreover, right ventricular volume overload due to pulmonary regurgitation after surgery for TOF also leads to increased NT-proBNP levels. [44,45] NT-proBNP levels have been reported as a useful marker of HF in patients with single ventricular circulation after Fontan surgery.…”
Section: Review Articlementioning
confidence: 97%
“…In heart disease due to a left-to-right shunt, such as ASDs and VSDs, NT-proBNP levels are high when the Qp/Qs is high, and the fact that this decreases after surgery indicates that congestive HF due to volume overload may result in increased NT-proBNP levels. [41][42][43] Moreover, right ventricular volume overload due to pulmonary regurgitation after surgery for TOF also leads to increased NT-proBNP levels. [44,45] NT-proBNP levels have been reported as a useful marker of HF in patients with single ventricular circulation after Fontan surgery.…”
Section: Review Articlementioning
confidence: 97%
“…Sin embargo, hasta el momento actual no se ha descrito el comportamiento del péptido natriurético en la patología traumática cardíaca, por lo que, al tratarse de pacientes jóvenes y sin cardiopatía previa, podría estar razonablemente justificada su determinación. Sí están descritos casos que correlacionan valores de proBNP con la gravedad del shunt izquierda-derecha, PAP y dilatación de cavidades derechas en pacientes adultos y pediátricos con defectos septal auricular o ventricular no traumáticos 17,18 .…”
Section: Discussionunclassified
“…Ozhan and colleagues found the same relationship between BNP and the Qp:Qs ratio in their study of 35 children (mean age 70±129 weeks) with ventricular or atrial septal defects. Receiver operating characteristic analysis found that a plasma BNP cutoff of ≥20 pg/ml was 69% sensitive and 79% specific for a Qp:Qs of greater than 1.5 (Ozhan et al 2007). A number of studies of premature neonates found that BNP levels correlated with the degree of shunting across a patent ductus arteriosus and predicted hemodynamic significance as determined by echocardiography-based criteria (Choi et al 2005;Flynn et al 2005;Puddy et al 2002;Sanjeev et al 2005;Holmstrom and Omland 2002;da Graca et al 2006).…”
Section: Bnp In Pediatric Heart Diseasementioning
confidence: 99%